2020
DOI: 10.1093/carcin/bgaa089
|View full text |Cite
|
Sign up to set email alerts
|

Apelin enhances biological functions in lung cancer A549 cells by downregulating exosomal miR-15a-5p

Abstract: Apelin acts as a tumor promoter in multiple malignant tumors; however, its regulatory mechanism remains unclear. Previous studies have indicated that exosomes are pivotal to mediating tumor progression and metastasis. This study examined whether apelin enhances proliferation and invasion ability of lung cancer cells via exosomal miRNA. Lung cancer A549 cells overexpressing apelin and control vector were generated by lentiviral transfection. Exosomes were isolated from the culture supernatant of each cell group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Scavenger receptors CD163 and CD206, as cell surface markers, are highly expressed in M2 TAMs and are considered to be useful for distinguishing M2 phenotype from other M1 phenotype macrophages [28,29]. Notch signal transduction pathway, as a highly conservative signal transduction pathway, involves many cell biological processes including proliferation, angiogenesis, hypoxia, tumor stem cell activity, and epithelial-mesenchymal transformation (EMT), and can also be involved in inducing TAMs polarization [30][31][32]. The ligand of TLR (such as LPS or IFN-γ) can induce macrophages to polarize into M1 phenotype, promote inflammatory reaction, and kill tumor cells.…”
Section: Polarization and Typing Of Tamsmentioning
confidence: 99%
“…Scavenger receptors CD163 and CD206, as cell surface markers, are highly expressed in M2 TAMs and are considered to be useful for distinguishing M2 phenotype from other M1 phenotype macrophages [28,29]. Notch signal transduction pathway, as a highly conservative signal transduction pathway, involves many cell biological processes including proliferation, angiogenesis, hypoxia, tumor stem cell activity, and epithelial-mesenchymal transformation (EMT), and can also be involved in inducing TAMs polarization [30][31][32]. The ligand of TLR (such as LPS or IFN-γ) can induce macrophages to polarize into M1 phenotype, promote inflammatory reaction, and kill tumor cells.…”
Section: Polarization and Typing Of Tamsmentioning
confidence: 99%
“…Yang et al found that apelin-13 could promote lung adenocarcinoma cell proliferation and induced cell autophagy via extracellular signal-regulated kinases (ERK) 1/2 signaling (36). Ran et al discovered that apelin could promote lung cancer A549 cells proliferation and invasion by inhibiting exosomal miR-15a-5p (37). Interestingly, a recent study revealed that miR-195 could directly target apelin, thus inhibiting lung adenocarcinoma cell proliferation and invasion (38).…”
Section: Lung Cancermentioning
confidence: 99%
“…The results showed that the "Apelin signaling pathway", and "Oxytocin signaling pathway" were the main changed biological processes by analyzing the KEGG and GO pro les. Similarly, Jingjing Ran et al found that Aplin promotes biological functions in lung cancer cells by inhibiting exosome miR-15a-5p 17 . C Péqueux et al found that Oxytocin promotes the growth of human small-cell lung cancer, which is controlled by the mitogen-activated protein kinase pathway 18 .…”
Section: Discussionmentioning
confidence: 94%